Coral reef ecosystem services in the Anthropocene - Woodhead, Anna J.; Hicks, Christina C.; Norström, Albert V.; Williams, Gareth J.; Graham, Nicholas A. J. (Functional ecology, 2019)
Coral reefs underpin a range of ecosystem goods and services that contribute to the well‐being of millions of people. However, tropical coral reefs in the Anthropocene are likely to be functionally different from reefs in the past. In this perspective piece, we ask, what does the Anthropocene mean for the provision of ecosystem services from coral reefs? First, we provide examples of the provisioning, regulating, cultural and supporting services underpinned by coral reef ecosystems. We conclude that coral reef ecosystem service research has lagged behind multidisciplinary advances in broader ecosystem services science, such as an explicit recognition that interactions between social and ecological systems underpin ecosystem services. Second, drawing on tools from functional ecology, we outline how these social–ecological relationships can be incorporated into a mechanistic understanding of service provision and how this might be used to anticipate future changes in coral reef ecosystem services. Finally, we explore the emergence of novel reef ecosystem services, for example from tropicalized coastlines, or through changing technological connections to coral reefs. Indeed, when services are conceived as coming from social–ecological system dynamics, novelty in services can emerge from elements of the interactions between people and the ecosystem. This synthesis of the coral reef ecosystem services literature suggests the field is poorly prepared to understand the changing service provision anticipated in the Anthropocene. A new research agenda is needed that better connects reef functional ecology to ecosystem service provision. This research agenda should embrace more holistic approaches to ecosystem service research, recognizing them as co‐produced by ecosystems and society. Importantly, the likelihood of novel ecosystem service configurations requires further conceptualization and empirical assessment. As with current ecosystem services, the loss or gain of services will not affect all people equally and must be understood in the context in which they occur. With the uncertainty surrounding the future of coral reefs in the Anthropocene, research exploring how the benefits to people change will be of great importance. A plain language summary is available for this article. Plain Language Summary